A dieugenol-based epoxy monomer with high bio-based content, low viscosity and low flammability. (December 2021) - Zhang, Daqin; Jin, Shenglin; Wan, Jintao; Wang, Juanli; Li, Yuhu; Jin, Pujun; Hu, Daodao
Abstract: A renewable eugenol-based biphenyl bifunctional epoxy monomer (DEUEP) is synthesized via a facile method. Eugenol is coupled into 5, 5′-dieugenol and then glycidized to yield DEUEP with a potentially 100% biobased content in a high purity (96%). DEUEP displays a lower viscosity (9.2 vs. 20.6 Pa·s at 25 ℃) and a flow activation energy (60.4 ± 0.4 vs. 81.1 ± 0.4 kJ/mol) than a commodity bisphenol A-based epoxy prepolymer (E54) does. With a 3, 3′-diaminodiphenylsulfone (33DDS) hardener, DEUEP/33DDS is found to express the reactivity identical to E54/33DDS with a similar activation energy (~62 kJ/mol). The cured DEUEP/33DDS thermoset is systematically examined and compared with E54/33DDS in terms of dynamic mechanical properties, thermal stability, flammability, flexural, impact and shear properties, fracture behaviors, water resistance, and wettability. DEUEP/33DDS has a lower flammability as indicated by the increased limited oxygen index (26.4% vs. 22.1%), the decreased heat release rate (HRR), total heat release (THR) and heat capacity (HR) by 46%, 33% and 46%, respectively. DEUEP/33DDS has T g of 120.9 ℃, a storage modulus of 2.57 GPa (25 ℃), a higher char yield of 32.2% (750 ℃ in N2 ), and a higher water-contact angle of 110.6°. Graphical Abstract: ga1